Uji Deteksi Adulterasi Daging Babi (Sus scrofa domestica) pada Bakso Metode Loop-Mediated Isothermal Amplification - Rahma Micho Widyanto; Cleonara Yanuar Dini; Irma Sarita Rahmawati; Sekar Ramadhanti Putri; Amelia Nurdini Rozana; Sakinah Hilya Abida; Yunimar Yunimar (Indonesian Journal of Human Nutrition, 2021)
Composition adulteration in a product is still a serious problem. For that we need a DNA-based test method that is fast, specific and simple. In this study, a rapid test technique with the loop-mediated isothermal amplification method was applied to identify the presence of pork DNA in meatballs. Six primers were used for the identification of mitochondrial DNA cytochrome oxidase subunit II. Samples were prepared in the form of mixed beef meatballs containing pork with a concentration of 50; 5; 0.5; 0.05%, respectively. The results showed that the optimal concentration for primers was 4 pmol inner primers, 2 pmol loop primers, and 1 pmol outer primers. The LAMP reaction showed a change in color in the meatball sample with the pork mixture to the lowest concentration. The LAMP technique provides a faster test with the final result of on-the-spot color visualization so that it is potential to be developed as a quick detection kit for identification of halal food processed products